A Meta-Analysis on the Impact of Gamification over Students’ Motivation (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Controversy surrounds the effectiveness of educational gamification on learners’ motivation to study. Prior papers attempting to summarize the available empirical evidence on the topic encompass too many additional domains like the academic performance so that the motivational point is discentrated. Hence, the current meta-analysis aimed to synthesize research findings limited to the clearly stated impact of gamification on higher education students’ academic motivation. Results from random effects proportion meta-analysis applied to seven relevant studies with a total of 368 students showed a pooled proportion of 29.68%. In other words, game design elements incorporated into the learning activities were significantly motivating for only about one-third of participants. The assumption of homogeneity was violated for certain reasons. As part of the discussion, previous scholars’ efforts to identify moderating factors of successful gamification were overviewed, and their practicality was questioned. It is concluded that the issue of whether educational gamification can amplify students’ learning motivation remains an area for further research.